External Pressures on Accounting Study Programs: An Institutional Approach of Stakeholder Expectations - Cristina Circa; Alina Almasan; Adina Popa (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - What are the requirements and expectations of each class of external stakeholders? Is there any convergence between the identified expectations? Motivation - There is a large variety of stakeholder expectations that universities are confronted with in their permanent search for social legitimacy, acknowledgement and survival. In the case of accounting study programs, their strong relationships with practitioners and professional associations, as emphasized in previous research in accounting education in Central and Eastern European (CEE) countries, add to the expectations that need to be met. Idea - This paper explores external stakeholder expectations of accounting study programs provided by Romanian universities, in order to identify the elements to which these expectations converge. Data - Data was collected only from public documents (laws and regulations, reports, studies, press releases, websites of relevant bodies etc.). Tools - A review of relevant public documents has been performed. Findings - As expected, all stakeholders require quality. Still, they ascribe different meanings to quality, evaluate quality in different manners, and hence exert various pressures. More, we observed that all types of isomorphism: coercive, mimetic, normative, as well as competitive are involved in assuring quality and meeting expectations. Contribution - The study contributes to literature with a complex approach, employing stakeholder and institutional theory, in the context of the extensive environment of higher education. In terms of practice, by taking stock of stakeholder requirements and expectations, the study calls the attention of decision makers to stakeholder pressures and the need to adjust accounting study programs accordingly.
Keywords: I23; M40; 650; institutional theory; stakeholders; expectations; higher education; accounting study programs